IL1 Receptor Antagonist Gene IL1-RN Variable Number of Tandem Repeats Polymorphism and Cancer Risk: A Literature Review and Meta-Analysis - Zhang, Ying (Public Library of Science, 2012)
IL1 receptor antagonist (IL1RA) and IL1beta (IL1β), members of the pro-inflammatory cytokine interleukin-1 (IL1) family, play a potential role against infection and in the pathogenesis of cancers. The variable number of tandem repeats (VNTR) polymorphism in the second intron of the IL1 receptor antagonist gene (IL1-RN) and a polymorphism in exon 5 of IL1B (IL1B+3954C>T, rs1143634) have been suggested in predisposition to cancer risk. However, studies have shown inconsistent results. To validate any association, a meta-analysis was performed with 14,854 cases and 19,337 controls from 71 published case–control studies for IL1-RN VNTR and 33 eligible studies contained 7,847 cases and 8917 controls for IL1B +3954. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated from comparisons to assess the strength of the association. There was significant association between the IL1-RN VNTR polymorphism and the risk of cancer for any overall comparison. Furthermore, cancer type stratification analysis revealed that there were significantly increased risks of gastric cancer, bladder cancer and other cancer groups. Infection status analysis indicated that the H. pylori or HBV/HCV infection and IL1-RN VNTR genotypes were independent factors for developing gastric or hepatocellular cancers. In addition, a borderline significant association was observed between IL1B+3954 polymorphism and the increased cancer risk. Although some modest bias could not be eliminated, this meta-analysis suggested that the IL1-RN VNTR polymorphisms may contribute to genetic susceptibility to gastric cancer. More studies are needed to further evaluate the role of the IL1B+3954 polymorphism in the etiology of cancer.